2020
DOI: 10.1007/s40333-020-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the W-beam central guardrails on wind-blown sand deposition on desert expressways in sandy regions

Abstract: Many desert expressways are affected by the deposition of the wind-blown sand, which might block the movement of vehicles or cause accidents. W-beam central guardrails, which are used to improve the safety of desert expressways, are thought to influence the deposition of the wind-blown sand, but this has yet not to be studied adequately. To address this issue, we conducted a wind tunnel test to simulate and explore how the W-beam central guardrails affect the airflow, the wind-blown sand flux and the depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…BIO01, BIO3, BIO12, and BIO15 are important factors explaining the local environmental adaptation of the two Picea species. P. mongolica occupies the eastern edge of the Hunshandake sandy land, with concentrated stands on both the leeward and windward slopes of the Baiyinaobao sandy land, making it one of the preferred tree species for afforestation in China’s sandy lands [ 59 , 60 ]. Studies on the P. mongolica growth conditions and ecological requirements in sandy lands have shown that P. mongolica growth in June accounts for approximately 65% of its annual growth, with the water and thermal conditions in June determining its annual height increase, making seasonal precipitation particularly important for its growth [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…BIO01, BIO3, BIO12, and BIO15 are important factors explaining the local environmental adaptation of the two Picea species. P. mongolica occupies the eastern edge of the Hunshandake sandy land, with concentrated stands on both the leeward and windward slopes of the Baiyinaobao sandy land, making it one of the preferred tree species for afforestation in China’s sandy lands [ 59 , 60 ]. Studies on the P. mongolica growth conditions and ecological requirements in sandy lands have shown that P. mongolica growth in June accounts for approximately 65% of its annual growth, with the water and thermal conditions in June determining its annual height increase, making seasonal precipitation particularly important for its growth [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surface of roads is lower than that covered by pasture (Figure 1c). The soil of the road is exposed to strong winds without vegetation protection, and soil particles are crushed by vehicles and livestock, which accelerates the process of wind erosion on roads [23,25]. In addition, livestock affects the surrounding area of the road through trampling (Figure 1c), and both soil and vegetation factors decrease regularly along the road [33].…”
Section: The Influence Of Roads On Wind Erosionmentioning
confidence: 99%
“…The road surface is lower than the surrounding grassland and agricultural land, with wind erosion rates of approximately 2.9-3.8 cm yr −1 caused by vehicles [23], and the emission potential of PM 10 increases by 9-160 times under the disturbance of human activities such as traffic [24]. Furthermore, roads also have an impact on the vegetation and soil structures in the surrounding area [25], which shows that the erosion intensity decreases with the distance from the road [26][27][28]. These studies illustrate that the distribution of roads exacerbates regional erosion and dust emissions, which are affected by road characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In sandy areas in particular, the disturbance of the blown sand activity is more intense after construction. Furthermore, the near-surface wind speed, wind field, and sand transport rate are significantly changed, as are the erosion, transport and accumulation conditions of wind-blown sand flow [ 4 , 5 ]. Therefore, preventing and controlling the harm caused by wind-blown sand by relying on the road surface to transport sand is difficult.…”
Section: Introductionmentioning
confidence: 99%